Designing Collective Artist Residencies: Cultivating imaginative disruptions and light-heartedness in times of gravity. (2021) - Eernstman, Natalia; Pearson, Kelli Rose; Wals, Arjen Evert Jan; Bjurström, Åse Eliason; Vrieze, Anke de
No abstract available